2002
DOI: 10.1046/j.0014-2956.2002.02742.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding and refolding studies of frutalin, a tetrameric d‐galactose binding lectin

Abstract: Protein refolding is currently a fundamental problem in biophysics and molecular biology. We have studied the refolding process of frutalin, a tetrameric lectin that presents structural homology with jacalin but shows a more marked biological activity. The initial state in our refolding puzzle was that proteins were unfolded after thermal denaturation or denaturation induced by guanidine hydrochloride, and under both conditions, frutalin was refolded. The denaturation curves, measured by fluorescence emission,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It belongs to the jacalin-related lectins family, more precisely to the galactose-binding sub-family, as it presents high similarities in sequence, structure and sugar specificity with the jacalin lectin (the galactose-specific lectin of A. integrifolia seeds-jackfruit, the first member of this family to be identified) [5, 6, this work]. Frutalin also presents functional properties identical to jacalin; however, it has a more noticeable biological activity than the jackfruit lectin, as shown by its higher hemagglutination activity [7]. Previous studies have shown that frutalin plays an important role in many biomedical applications.…”
Section: Introductionmentioning
confidence: 86%
“…It belongs to the jacalin-related lectins family, more precisely to the galactose-binding sub-family, as it presents high similarities in sequence, structure and sugar specificity with the jacalin lectin (the galactose-specific lectin of A. integrifolia seeds-jackfruit, the first member of this family to be identified) [5, 6, this work]. Frutalin also presents functional properties identical to jacalin; however, it has a more noticeable biological activity than the jackfruit lectin, as shown by its higher hemagglutination activity [7]. Previous studies have shown that frutalin plays an important role in many biomedical applications.…”
Section: Introductionmentioning
confidence: 86%
“…The lectin from A. incisa, which is named frutalin (FTL), has been isolated and characterized (Moreira et al, 1997), and its refolding process has been studied using thermal and chemical denaturation (Campana et al, 2002). It belongs to the jacalin lectin-related family (Moraceae family) and has an affinity for -d-galactose monosaccharides and complex carbohydrates that contain Gal 1-3 glycans (Moreira et al, 1997;Nobre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The β chain is not visible due to its low molecular weight (2.1 kDa; Oliveira et al, 2008). In its native form, FTL is a tetrameric molecule, consisting of four monomers bound by non-covalent linkages, each containing one β and one α chain, forming four sugar-binding sites, with a predominantly β sheet conformation (Moreira et al, 1998; Campana et al, 2002) and an apparent molecular mass of 48–49 kDa (Moreira et al, 1998; Oliveira et al, 2008). FTL is a robust protein as it is stable up to 60°C and very resistant to chemical denaturation (Campana et al, 2002).…”
Section: Outlinementioning
confidence: 99%